Investigating Academic Writing in EFL Contexts: Students’ Voices on Complexities and Coping Strategies - Sania Alinda Mouli Asnas; Mutmainnah Mustofa; M. Faruq Ubaidillah (Universitas Islam Negeri Walisongo Semarang, 2022)
This research aimed to investigate students’ voices regarding the complexities that contribute to challenges and the coping strategies that address academic writing challenges they use in academic writing. Through a qualitative method, four female students majoring in English Education in the eighth semester at a private university in Indonesia were chosen as participants in this study's interview. Data analysis techniques employed include analyzing the data, coding the data, and interpreting the data. The findings indicated that twelve complexities contributed, namely learners’ low motivation, lack of lecturers’ feedback, lack of translation, lack of references, lack of time, lack of research background, low students' self-confidence, lack of experience in writing, lack of proficiency in reading, lack of critical thinking skill, lack of proper preparation in writing, and lack of a supportive writing learning environment. Students used twelve coping strategies for organization, ideas development, vocabulary, grammar, and mechanics. These strategies included exercises, feedback, reading academic papers, extensive reading, Google Translate, QuillBot, Grammarly, and Mendeley for arranging academic style. The implication of this research has been discussed here.